Narrating Student’s English Learning Experiences Through English Series and Movies - Enggar Bagas Dewantara; Arilia Triyoga (Universitas Islam Negeri Palopo, 2025)
English movies and series are used effectively by teachers and students to stimulate and develop their English proficiency. The significance of using movies and series in language teaching and learning has been discussed by academic experts, yet still there is a gap in research regarding students' specific experiences and the improvement of their English abilities through the use of English movies and series. This study aimed to analyze students’ English learning experiences through English series and movies and to analyze the improvement of students’ English ability through English series and movies. This type of research is qualitative research with a narrative inquiry approach. It uses Narrative Inquiry Design to collect data such as in-depth interviews. The respondent of this study was a high-performance student who was an awardee of International Credit Transfer (ICT) for one semester in Malaysia. This research was conducted in Universitas Ahmad Dahlan, Indonesia, from May 2022 until July 2023. The result showed that the respondent's experience with English series and movies highlights the benefits of self-directed learning in improving language skills. By regularly watching content in English, she improved her listening and speaking abilities, exposed herself to different accents and expressions, and used subtitles to improve vocabulary and writing. This consistent engagement with authentic materials significantly contributed to her language development.